Peasant Families’ Journeys from Algeria to Mashriq (1880s–1890s): Personal Correspondence, Migration Networks, and Resettlement - Salma Hargal (Mashriq & Mahjar)
In this article, Salma Hargal analyzes the journey of impoverished Algerians who became settlers on state-granted lands within the framework of Ottoman immigration policies and who acquired Ottoman citizenship under the 1869 Nationality Law. Drawing on a diverse range of sources—including confiscated letters,  Ottoman archival documents, and French colonial and diplomatic correspondences and reports—Hargal reconstructs the trajectories of two families who emigrated to Damascus and Tiberias in Ottoman Palestine. Their experiences shed light on the interplay between personal networks, the support provided by trans-imperial family,  Ottoman migration policies, and the challenges posed by ambiguous legal statuses.